Implementasi Pentasyarufan Dana Zakat melalui Program Kesehatan bagi Masyarakat Miskin di Lazismu Klaten - Habib Ismail; Fachruddin Edi Nugroho Saputro (Universitas Muhammadiyah Klaten, 2025)
The community service activity titled “Implementation of Zakat Fund Distribution through Health Programs for the Poor in Lazismu Klaten: Free Modern Laser Circumcision” was organized by Universitas Muhammadiyah Klaten to improve access to healthcare services for the poor. Klaten Regency was selected as the program location due to its relatively high poverty rate, recorded at 12.04% as of March 2024, affecting approximately 141,840 individuals. This data reflects the urgent need for social and faith-based interventions to alleviate the economic burden faced by underprivileged families. Lazismu collected and distributed zakat funds to support a free circumcision program using safe and efficient laser technology. The implementation team formulated strategies through focus group discussions with health partners, then conducted outreach and selected participants from low-income families. A total of 60 children received free circumcision services. The results showed a reduction in healthcare costs, improved health literacy among beneficiaries, and strengthened the role of zakat in contributing to public health and social development.